Dural tears with cauda equina herniation following percutaneous endoscopic lumbar discectomy: a case report and literature review - Xie, Shiwei; Luo, Mingwei; Xiao, Heng (Frontiers in Surgery, 2024)
Lumbar disc herniation (LDH) is a prevalent condition that severely impacts patients' quality of life and work capacity. Traditional surgical treatments like laminectomy, while effective, involve significant invasiveness and potential complications, including long-term spinal instability and recurrent symptoms. With the advancement of minimally invasive techniques, percutaneous endoscopic lumbar discectomy (PELD) has become a popular option due to its reduced trauma and faster recovery. However, PELD, while beneficial, carries risks, including complications that may not be immediately evident. This report presents the case of a 60-year-old female patient who underwent PELD for L4/5 disc herniation but experienced significant postoperative complications, including increased pain and neurological symptoms. Initial conservative management failed, and further investigations suggested possible postoperative infection, though this was later ruled out through surgical exploration and bacterial cultures. The patient subsequently underwent open surgical exploration, which revealed extensive tissue damage and required additional interventions, including a minimally invasive lateral anterior approach for stabilization and fusion (MIS-OLIF). Postoperative recovery was successful, with complete symptom resolution and stable spine alignment at a six-month follow-up. This case highlights the complexity of managing PELD-related complications and underscores the importance of thorough diagnostic evaluation and the potential need for additional surgical interventions to ensure long-term patient outcomes.